The impact of French foreign policy towards Africa on the external migration policy of the European Union - Onder Aytac Afsar; Abdelhafid El-Hayanı (Acta Politica Polonica, 2023)
This article analyses France’s foreign policy towards Africa from a realist perspective. It identifies how this policy creates a state of inequality in terms of Franco-African relations through the Francafrique system and how the long-term policy’s consequences have led to negative impacts on the European Union’s External Migration Policy towards the world’s poorest continent. This inequality in terms of Franco-African relations is explained from the perspective of other theories including the Dependency theory and Capital System that highlight inequality between the Global South and the Western world. As a result, it is highly important to examine the volumes of illegal migrant flows to the European territories crossing the Mediterranean Sea from the Sahel and Sub-Saharan Francophone countries to understand how the EU’s External Migration Policy is impacted by the foreign policy adopted by one of the most powerful players in the international system and EU’s member states towards Africa.